Implementing Task-Based Instruction to Facilitate Language Learning: Moving Away from Theory - Aileen Griffiths (TEFLIN Journal: A publication on the teaching and learning of English, 2001)
The use of tasks has gained growing acceptance in the field of language teaching. In the task-based teaching, the organization of th language classroom is learner-centered and the learning activities involve communicative language use. This paper discuss task-based teaching by presenting a brief overview of its underlying rationales. The rationales for incoporating task-based activities are dirived from the psycholinguistic and pedagogical perpectives. Some practical insights in this paper might be useful for English teachers and language experts.